Latest methodological contributions and future perspectives in Spanish-FL/SL manuals - González Sánchez, María; Andión Herrero, María Antonieta (Círculo de Lingüística Aplicada a la Comunicación, 2021)
The teaching of Spanish-FL/SL has an important tradition of educational materials. Its wide range of current works allows students, teachers and academic authorities to satisfy, among others, their methodological expectations. All pursue, in any case, the acquisition-learning of linguistic aspects and communication skills that guarantee the mastery of Spanish. In the assessment of the manuals, the methodology has a special importance because it will be decisive to achieve the purposes of teaching and learning. We present the results of the application of an original analysis model (instruments, work method and analysis criteria) of recognized current manuals of Spanish-FL, with different degrees of adhesion to Communicativism. Likewise, we reflect on those aspects that can be improved, and offer, according to our criteria and experience, innovative alternatives in the field of teaching and learning second languages.
Keywords: Spanish-FL/SL teaching-learning methodology; Task-based approach; Communicative approach; Action-oriented approach,; Eclecticism